Epidemiology of enteroviral meningoencephalitis in neonates and young infants. (23rd December 2013) - March, Brayden; Eastwood, Keith; Wright, Ian M; Tilbrook, Lynelle; Durrheim, David N
<x xml:space="preserve">Abstract</x> Aim To describe the epidemiology of enteroviral meningoencephalitis in northern New South Wales, Australia, with a specific focus on neonatal and young infant cases. Methods A retrospective review of PCR‐confirmed enteroviral meningoencephalitis cases in the Hunter New England Local Health District of northern NSW was conducted for the period 2008–2012. Results One hundred nine patients met the case definition. There was summer seasonality, with 50% (55/109) of cases occurring between December and February. Neonates and young infants (<3 months of age) accounted for 42% (46/109) of cases, with 20% (9/46) being premature births. Fever (83%) was the most common presentation in this age group, followed by irritability (40%), feeding difficulties (40%) and rash (17%). All received at least one antibiotic during their admission, with 26% (12/46) also treated empirically with acyclovir. There was one death. Where testing was undertaken, cerebrospinal fluid (CSF) protein levels were high in 90% (28/31) of neonates and young infants, but the CSF white cell count was variable, with 57% <10/mm3 and 21% >100/mm3. Conclusion Early diagnosis of enteroviral meningoencephalitis could alter management, potentially reducing the period of treatment with empirical antimicrobials and permitting earlier discharge.